2015
DOI: 10.1038/nature14190
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient-sensing mechanisms and pathways

Abstract: PREFACE The ability to sense and respond to fluctuations in environmental nutrient levels is a requisite for life. Nutrient scarcity is a selective pressure that has shaped the evolution of most cellular processes. Different pathways that detect intracellular and extracellular levels of sugars, amino acids and lipids, and surrogate metabolites, are then integrated and coordinated at the organismal level via hormonal signals. During food abundance, nutrient sensing pathways engage anabolism and storage, and sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
794
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 918 publications
(838 citation statements)
references
References 113 publications
9
794
0
4
Order By: Relevance
“…It is increasingly appreciated that, in addition to their degradative functions, lysosomes act as a signaling platform that integrates various metabolic inputs and initiates signals that regulate numerous downstream targets. Notably, the Rag GTPases are peripheral membrane proteins of the lysosome that communicate intracellular nutrient availability to the mTORC1 signaling pathway (28). Staining of mouse brains for RagC revealed that this important lysosome-associated signaling protein colocalized with LAMP1 on lysosomes in the cell bodies of both WT and mutant neurons (Fig.…”
Section: Multiple Lysosomal Proteins Are Enriched Within Plaque-assocmentioning
confidence: 99%
“…It is increasingly appreciated that, in addition to their degradative functions, lysosomes act as a signaling platform that integrates various metabolic inputs and initiates signals that regulate numerous downstream targets. Notably, the Rag GTPases are peripheral membrane proteins of the lysosome that communicate intracellular nutrient availability to the mTORC1 signaling pathway (28). Staining of mouse brains for RagC revealed that this important lysosome-associated signaling protein colocalized with LAMP1 on lysosomes in the cell bodies of both WT and mutant neurons (Fig.…”
Section: Multiple Lysosomal Proteins Are Enriched Within Plaque-assocmentioning
confidence: 99%
“…Autophagy is a hierarchical process involving the activation of ULK1, the initiating kinase, and many downstream events such as Beclin 1 complex activation and LC3 lipidation [3] . It has been well established that, during amino-acid starvation, mTOR, the master nutrient sensor, dissociates from and in turn activates ULK1 kinase [4] .Interestingly, upon energy starvation such as glucose depletion, the main energy sensor AMPK activates ULK1 through antagonizing mTOR-mediated ULK1 inhibitory phosphorylation [5] . It is generally believed that starvation induces non-selective autophagy that targets non-essential cellular components for degradation to provide building blocks for cellular survival in unfavorable conditions.…”
mentioning
confidence: 99%
“…Autophagy is a hierarchical process involving the activation of ULK1, the initiating kinase, and many downstream events such as Beclin 1 complex activation and LC3 lipidation [3] . It has been well established that, during amino-acid starvation, mTOR, the master nutrient sensor, dissociates from and in turn activates ULK1 kinase [4] .…”
mentioning
confidence: 99%
“…5,6 The PI3K/AKT/mTORC1 molecular pathway axis has been described as a master negative regulator of autophagy via its ability to control the initiation steps of this catabolic process. [7][8][9][10][11] Apart from regulating autophagosome initiation, mTORC1 has been recently suggested to control later stages of the autophagic process and specifically autophagosome maturation in nutrient-replete conditions. 12 However, it has been suggested that autophagy can be also regulated via mTOR-independent mechanisms.…”
Section: Introductionmentioning
confidence: 99%